Public Preferences for Longleaf Pine Restoration Programs in the Southeastern United States. Issue 3 (15th April 2021) - Oluoch, Sydney; Lal, Pankaj; Wolde, Bernabas; Susaeta, Andres; Soto, Josè R; Smith, Meghann; Adams, Damian C
Abstract: Longleaf pine (LLP) ( Pinus palustris Mill.) is well known for its role in supporting healthy ecosystems in the southeastern (SE) United States (US). The decline of LLP forest ecosystems has led to a consensus among stakeholders that restoration efforts are needed. However, there is still a lack of robust understanding of the utilization of nonmarket ecosystem services of LLP forests. These challenges have presented major barriers to landowner acceptance of subsidized LLP restoration programs. Understanding the tradeoffs between forest ecosystem services is critical to restoring LLP in the SE US. This study employs the best-worst choice (BWC) method to assess public preferences toward hypothetical LLP restoration programs that consider ecosystem services such as recreation, timber production, carbon sequestration, water yield, and wildlife diversity. We surveyed a representative sample of n = 953 respondents from Alabama, Mississippi, Georgia, and Florida, and results showed that residents in all four states are willing to pay for LLP restoration, with the highest average willingness to pay (WTP) for forest recreation ($20.39), followed by red-cockaded woodpecker (RCW) conservation ($13.37) and carbon sequestration ($13.32). This research provides important public preference information on ecosystem services that is critical in forming sustainable LLP restoration programs.